Study on the internal field and conduction mechanism of atomic layer deposited ferroelectric Hf0.5Zr0.5O2 thin films. Issue 24 (28th June 2015) - Park, M. H.; Kim, H. J.; Kim, Y. J.; Moon, T.; Kim, K. D.; Lee, Y. H.; Hyun, S. D.; Hwang, C. S.
<x xml:space="preserve">Abstract</x> The effects of the internal field and conduction mechanism of carriers in ferroelectric Hf0.5Zr0.5O2 thin films are systematically investigated by controlling the in-depth profile of oxygen vacancy concentrations.